2021
DOI: 10.1021/acs.est.1c01705
|View full text |Cite
|
Sign up to set email alerts
|

Tracking POPs in Global Air from the First 10 Years of the GAPS Network (2005 to 2014)

Abstract: The Global Atmospheric Passive Sampling (GAPS) network, initiated in 2005 across 55 global sites, supports the global monitoring plan (GMP) of the Stockholm Convention on Persistent Organic Pollutants (POPs) by providing information on POP concentrations in air on a global scale. These data inform assessments of the long-range transport potential of POPs and the effectiveness evaluation of chemical regulation efforts, by observing changes in concentrations over time. Currently, measurements spanning 5–10 sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 42 publications
7
45
0
1
Order By: Relevance
“…In comparison, only 60% of the Herkert-modelled median PAS concentrations are within a factor of 3 of the corresponding AAS concentrations due to signicantly higher concentrations for the majority of SVOCs at both Birkenes and Pallas when compared to the Harner-modelled concentrations. This discrepancy was unexpected, as previous studies have found negligible differences in the output concentrations between the two models for most sites/compounds, 8,34 despite their different input parameters. Similar negligible differences were observed in this study at the other four sites, with median PAS concentrations from the two models falling within a factor of 1.5 of each other for all SVOCs at Košetice, Råö, Stórhöf+i, and Zeppelin.…”
Section: Concentrations and Sampling Ratesmentioning
confidence: 62%
See 4 more Smart Citations
“…In comparison, only 60% of the Herkert-modelled median PAS concentrations are within a factor of 3 of the corresponding AAS concentrations due to signicantly higher concentrations for the majority of SVOCs at both Birkenes and Pallas when compared to the Harner-modelled concentrations. This discrepancy was unexpected, as previous studies have found negligible differences in the output concentrations between the two models for most sites/compounds, 8,34 despite their different input parameters. Similar negligible differences were observed in this study at the other four sites, with median PAS concentrations from the two models falling within a factor of 1.5 of each other for all SVOCs at Košetice, Råö, Stórhöf+i, and Zeppelin.…”
Section: Concentrations and Sampling Ratesmentioning
confidence: 62%
“…21 Yet studies have shown that when turbulent airflow conditions exist within the sampler ( e.g. , when the external wind speed exceeds 4.0 m s −1 ), the dependency of R S on v ex is stronger, ranging from sub-linear ( α = 0.63), 34 to linear ( α = 1), 16,19 or greater than linear ( α > 1). 15,20,39,40 As a result, the constant square-root shape of the dependency, regardless of extremely high wind speeds, leads to an underestimation of modelled R S over periods of strong wind.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations